Achieving intracellular cytokine staining assay concordance on two continents to assess HIV vaccine‐induced T‐cell responses. Issue 5 (22nd July 2022) - Dintwe, One B.; De Rosa, Stephen C.; Huang, Yunda; Flach, Britta S.; Manso, Bryce; Carter, Don; Omar, Faatima Laher; Schwedhelm, Katharine V.; Yu, Chenchen; Lu, Huiyin; Morris, Daryl; Kee, Jia Jin; et al.
Abstract: The HIV Vaccine Trials Network (HVTN) conducts clinical trials on 4 continents in pursuit of a safe and effective HIV vaccine. Cellular immune responses to vaccination that define vaccine immunogenicity and/or immune correlates of protection can be measured using multiparameter intracellular cytokine staining (ICS) assays. The HVTN cellular immunology laboratory, located in Seattle, WA, conducts ICS assays for vaccine trials according to Good Clinical Laboratory Practices (GCLP). In 2013, the HVTN established a second GCLP compliant cellular immunology laboratory in Cape Town, South Africa to assess vaccine immunogenicity for HVTN trials conducted on the African continent. To ensure ICS readouts in the 2 laboratories were directly comparable, we conducted concordance testing using PBMC from healthy controls and vaccine trial participants. Despite standardized procedures and instrumentation, shared quality control measures and quality assurance oversight, several factors impacted our ability to obtain close agreement in T‐cell responses measured in the 2 laboratories. One of these was the type of fetal bovine serum (FBS) used in the assay, which impacted lymphocyte cell viability and background responses. In addition, the differences in supernatant removal technique also significantly affected our ability to detect positive responses to vaccine antigens. Standardization of these factors allowed us to achieve and maintain ICS assay concordance across the 2 laboratories over multiple years, accelerating our efforts to evaluate HIV vaccines. The insights gained in this process are valuable for assay transfer efforts by groups of investigators that need to directly compare data generated in different laboratories around the globe. Graphical Abstract: Outcomes of quality control for achieving inter‐lab concordance of the ICS assay.